Prevalence of post-traumatic stress disorder risk post-COVID-19 in 12 countries in Latin America: a cross-sectional survey - Mejia, Christian R.; Serna-Alarcón, Víctor; Vilela-Estrada, Martín A.; Armada, Jose; Ubillus, Milward; Beraún-Barrantes, Jose; Álvarez-Risco, Aldo; Del-Aguila-Arcentales, Shyla; Davies, Neal M.; Yáñez, Jaime A. (Frontiers in Public Health, 2024)
Introduction Latin America was the region most affected by COVID-19 in the second quarter of 2020, and consequently, the impact on mental health requires evaluation. The aim of this study was to assess the risk of post-traumatic stress disorder (PTSD) caused by bereavement due to COVID-19 in 12 countries in Latin America. Methods The current study was an analytical cross-sectional study. Validated tests were applied for PTSD, depression, anxiety, and stress (DASS-21), questions about the respondent’s condition or their environment, and demographic questions, as well as the length of the mourning period of suffering. Results The outcomes demonstrated that the PTSD risk increased for women (p < 0.001), when a friend or acquaintance had COVID-19 (p = 0.002), when a close relative died from COVID-19 (p = 0.010), having severe depression (p <0.001), severe anxiety (p <0.001), severe stress (p <0.001), residing in Chile (p <0.001), Paraguay (p <0.001), Bolivia (p <0.001), Costa Rica (p <0.001) or El Salvador (p = 0.005). On the other hand, there was less risk of PTSD at an older age (p <0.001) or if respondents had a sentimental partner (p = 0.025). In the case of severe PTSD, there was a greater gender risk for women (p <0.001), a close relative dying from COVID-19 (p = 0.017), having severe depression (p <0.001), severe anxiety (p <0.001), severe stress (p <0.001), residing in Chile (p <0.001), Paraguay (p <0.001), Bolivia (p <0.001) and Costa Rica (p = 0.002). It was also observed that there was less risk of severe PTSD at an older age demographic (p <0.001). Discussion It can be concluded that the percentages of PTSD are high in its clinical presentation as severe, especially among Latin American women.